Diversity of phenanthrene and benz[a]anthracene metabolic pathways in white rot fungus Pycnoporus sanguineus 14. (October 2018) - Li, Xuanzhen; Pan, Yanshuo; Hu, Sheng; Cheng, Yongxia; Wang, Youjing; Wu, Kun; Zhang, Shimin; Yang, Suqin
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are a group of persistent organic compounds. White rot fungi (WRF) have attracted much attention due to their strong capabilities for the initial transformation of PAHs. To better understand the metabolic pathway of PAHS by WRF in the presence of ligninolytic enzymes and cytochrome P450 monooxygenase (P450s), degradation by a high laccase-producing fungus, Pycnoporus sanguineus 14, was examined in detail. This strain with high laccase activity (2516.7 U L −1 ) exhibited 45.6% biodegradation of phenanthrene (PHE) and 90.1% of benz[a]anthracene (BAA) under in vivo conditions. Gas chromatography–mass spectrometry (GC-MS) was used to identify 2-methylphenol as the product of PHE, and benz[a]anthracene-7, 12-dione, 2, 3-dihydroxy-3-phenylpropanoic acid and citramalic acid were identified as products of BAA. The results of an in vitro experiment indicated that the strain could initially transform PHE to 2-dibenzofuranol by intracellular enzymes containing P450s, or 9, 10-phenanthrenedione by extracellular laccase, and could initially transform BAA to benz[a]anthracene-7, 12-dione via extracellular laccase. Highlights: The fungus could produce relative high laccase production. The fungus could biodegrade phenanthrene and benz[a]anthracene. Phenanthrene was initially transformed via laccase and P450s. Benz[a]anthracene was initially transformed via laccase.